Bridging gaps in research and practice for early warning systems: new datasets for public response - Pescaroli, Gianluca; Dryhurst, Sarah; Karagiannis, Georgios Marios (Frontiers in Communication, 2025)
Early warning systems (EWSs) are essential for disaster and crisis response, applicable across a wide range of hazards and threats. They are increasingly recognized as pivotal in cross-disciplinary contexts, where diverse expertise is required to manage cascading, compound, and interconnected risks holistically. Despite their critical role, significant gaps persist in understanding the interplay between the technical, social, and organizational elements that underpin effective systems. Drawing on insights from the literature and our work on global datasets, such as the World Risk Poll, this comment paper highlights four key areas: (1) leveraging public behaviors and responses to enhance warning effectiveness; (2) understanding the role of trust in information sources and its influence on warning reception; (3) identifying limitations in existing analyses; and (4) addressing operational challenges such as data accessibility and harmonization. We propose a coherent approach that utilizes multi-country surveys to establish a common benchmark for addressing these issues, identifying shared patterns across diverse geographies, and improving the management of complex events and cross-border crises. This benchmarking effort could reveal actionable insights into regional drivers of EWS effectiveness, ultimately fostering greater international cooperation and advancing the socio-technical integration of disaster risk knowledge into operational resilience.